Pengujian Fenomena Underpricing Dengan Studi Eksperimen - Dedhy Sulistiawan (Universitas Airlangga, 2010)
The purpose of this study is to examine the impact of conflict of interest to the level of IPO price determined by managers. This experiment divides treatment group (the group of participants who have economic benefit from their decision making), and control group (groups with no economic benefit from their decision making). In experiment scenario for treatment group, the managements of IPO companies tend to decrease the price of IPO in order to get financial benefit. Using experimental design, this research shows that participants in treatment group determine lower IPO price than control group. This evidence confirms IPO phenomenon around the world. This research also makes supplementary analysis. The results show that alternative statistical test using GPA and gender of participants as control variable are not statistically significant. It means that the level of IPO price isn’t determined by GPA and Gender, but conflict of interest.